2009
DOI: 10.14429/dsj.59.1540
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Characterisation of Materials by Swift Heavy Ions

Abstract: Swift heavy ions (SHI) available with 15 million Volt Pelletron accelerator at Inter University Accelerator Centre (IUAC) Delhi, formerly known as Nuclear Science Centre, (NSC), provide a unique opportunity to researchers for accelerator based materials science research. The major research areas can be broadly categorised as electronic sputtering, interface modifications, synthesis and modification of nanostructures, phase transitions and ion beam-induced epitaxial crystallisation. In, general, SHI irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…An interesting characteristic of the ion insulator interaction is that it produces a columnar type of defect along its path (called as latent ion track) [26]. The final highest density of defects is observed at depths close to the ion range, which is a characteristic of heavy ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting characteristic of the ion insulator interaction is that it produces a columnar type of defect along its path (called as latent ion track) [26]. The final highest density of defects is observed at depths close to the ion range, which is a characteristic of heavy ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] D. Avasthi et al 27 reported that when an energetic ion penetrates into any material, it loses energy mainly by two independent processes: (i) elastic collisions with the nuclei, known as nuclear energy loss (dE/dx)n, which dominates at an energy of about 1 keV per amu, and (ii) inelastic collisions of the highly charged projectile ion with the atomic electrons of the matter, known as electronic energy loss (dE/dx)e, which dominates at an energy of about 1 MeV per amu or more. Swi heavy ion irradiation (SHII) of nanostructures has induced changes in size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…SHI during their passage through material result in excitation and ionization of the atoms by inelastic collisions (called as electronic energy loss, S e ) or displace them by elastic collisions (nuclear energy loss, S n ). These are known to result in production of defects in the target [26]. The shape of the defects introduced by SHI irradiation depends on the S e of the impinging ions.…”
Section: Introductionmentioning
confidence: 99%
“…In complex system like ferrites; where cations reside in two different sublattices, the defects can disturb the arrangement of cations which may result in significant effects on magnetic properties including the magnetic anisotropy. The advantage of SHI irradiation is that the properties can be locally and controllably changed depending upon the electronic energy loss and fluence values in the target materials [26]. The present study focuses on the modification of magnetic anisotropy in CoFe 2 O 4 thin films by SHI irradiation using 200 MeV Ag +17 ions at different fluences.…”
Section: Introductionmentioning
confidence: 99%